Germination of shrub species from Chinese subtropical forests: implications for restoration - Bhatt, A.; Daibes, L. F. [UNESP]; Chen, X.; Gallacher, D. J. (Wiley, 2023)
Incorporating native shrubs into restoration projects can improve biodiversity conservation and enhance the sustainability of ecosystem functions. Shrubs grow under different forest canopy structures, having varied microclimatic conditions according to forest type and composition. Currently, there is a lack of information on propagation from seed and planting material availability for the utilization of shrubs in forest restoration. In the present study, we evaluated the effects of temperature and light on germination of ten shrub species (Ardisia japonica, Callicarpa cathayana, Callicarpa giraldii var. subcanescens, Deutzia schneideriana, Fraxinus sieboldiana, Hydrangea chinensis, Maesa japonica, Rhododendron simsii, Spiraea japonica var. fortunei and Weigela japonica var. sinica) occurring in subtropical forests in China. No seeds of any species germinated in the coolest thermal regime (5/10 °C), while optimal temperature requirements varied from 10/20 °C to 25/35 °C. Seeds of small-seeded species had higher germination percentages in the light treatments, while larger seeds were not photoblastic. There was no relationship between germination in the light and the seed shape index. Our results may assist in identification of seed traits and suitable shrub species for restoration in specific forest types, thus aiding native forest recovery of structure and composition. Successful recovery leads to enhanced biodiversity, reestablishment of microhabitats and ecological interactions in the forest understorey.
Keywords: Germination; restoration; seedling; shrub; subtropics